Current and future challenges in stabilization techniques applied to particulate foods: a review - Rohini Dhenge; Arjun Mohanakumar; Massimiliano Rinaldi (Discover Food)
Abstract Stabilization of foods containing particulates is a critical aspect of modern food processing industries, and extensive research has highlighted the challenges and innovations in this topic. As consumer demand for nutritious, high-quality, affordable food options continues to rise, the development of advanced processing technologies has become increasingly important. These technologies must not only preserve the structural integrity of particulate-containing foods but also ensure product quality, safety, and shelf life. Addressing these needs is essential for meeting the expectations of health-conscious and value-driven consumers of today. The diversified low, medium, and high-viscosity foods containing particulates are complex and vary by processing method. This challenge has driven extensive research using analytical techniques, numerical and mathematical modeling, and computer simulations to better understand particulate behavior. The present review introduces the perspectives and their potential about the current important aspects regarding the fundamental mechanisms, stabilization techniques, critical parameters, their effects on the final quality and future perspectives of particulate foods with regard to the batch/in-container, continuous, aseptic, thermal-non-thermal, and other innovative processes associated with particulate foods. The data collection of stabilization is still in improvement, a few conflicting trends have been accounted for, essential further clarification and rapid development of techniques are crucial in the field of particulate foods. However, the real challenge is the formation of a microbiologically safe operation for particulates, without sacrificing the essential quality factor of stability, with a minimal detrimental impact on food.